Design Science Research. Cases - vom Brocke, Jan.; Hevner, Alan.; Maedche, Alexander; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2020)
Design Science Research is a powerful paradigm enabling researchers to make important contributions to society and industry. Simply stated, the goal of DSR is to generate knowledge on how to find innovative solutions to important problems in the form of models, methods, constructs and instantiations. Over the past 20 years, the design science research (DSR) paradigm has developed into an established paradigm in Information Systems Research and it is of strong uptake in many other disciplines, including Management Science and Computer Science. This book provides a collection of twelve DSR cases, presented by experienced researchers in the field. It offers readers access to real-world DSR studies, together with the authors’ reflections on their research processes. These cases will support researchers who want to engage in DSR, and represent a valuable addition to existing introductions to DSR methods and processes. Readers will learn from the hands-on experiences of respected experts who have conducted extensive DSR in a range of application contexts.
Introduction -- Part I: DSR in Information Management -- Part II: DSR in Information Systems Development -- Part III: DSR in Process Management -- Part IV: DSR in Knowledge Management -- Part V: DSR in Application Domains.
Keywords: elektronické knihy; electronic books; Business information services; Computer networks .; Electronic commerce; Computer science; Business Information Systems; Computer Communication Networks; E-Business.; e-Commerce and e-Business.; Theory of Computation